Effects of alternating elliptical chamber on jet impingement heat transfer in vane leading edge under different cross-flow conditions. (30th September 2021) - Xiao, K.; He, J.; Feng, Z.
ABSTRACT: This paper proposes an alternating elliptical impingement chamber in the leading edge of a gas turbine to restrain the cross flow and enhance the heat transfer, and investigates the detailed flow and heat transfer characteristics. The chamber consists of straight sections and transition sections. Numerical simulations are performed by solving the three-dimensional (3D) steady Reynolds-Averaged Navier–Stokes (RANS) equations with the Shear Stress Transport (SST) k – $ω$ turbulence model. The influences of alternating the cross section on the impingement flow and heat transfer of the chamber are studied by comparison with a smooth semi-elliptical impingement chamber at a cross-flow Velocity Ratio ( VR ) of 0.2 and Temperature Ratio ( TR ) of 1.00 in the primary study. Then, the effects of the cross-flow VR and TR are further investigated. The results reveal that, in the semi-elliptical impingement chamber, the impingement jet is deflected by the cross flow and the heat transfer performance is degraded. However, in the alternating elliptical chamber, the cross flow is transformed to a pair of longitudinal vortices, and the flow direction at the centre of the cross section is parallel to the impingement jet, thus improving the jet penetration ability and enhancing the impingement heat transfer. In addition, the heat transfer in the semi-elliptical chamber degrades rapidly away from the stagnation region, while the longitudinal vortices enhance the heat transfer further, making the heat transfer coefficient distribution more uniform. The Nusselt number decreases with increase of VR and TR for both the semi-elliptical chamber and the alternating elliptical chamber. The alternating elliptical chamber enhances the heat transfer and moves the stagnation point up for all VR and TR, and the heat transfer enhancement is more obvious at high cross-flow velocity ratio.